Challenges experienced by South Africa in attaining Millennium Development Goals 4, 5 and 6 - Fhumulani M. Mulaudzi; Seepaneng S. Phiri; Doriccah M. Peu; Mmamakwa L.S. Mataboge; Nkhensani R. Ngunyulu; Ramadimetja S. Mogale (AOSIS, 2016)
Background: Despite progress made by other countries worldwide in achieving Millennium Development Goals (MDGs) 4, 5 and 6, South Africa is experiencing a challenge in attaining positive outcomes for these goals. Objective and setting: To describe the challenges experienced by South Africa regarding the successful implementation of MDGs 4, 5 and 6. Methods: An integrative literature review was used to identify and synthesise various streams of literature on the challenges experienced by South Africa in attaining MDGs 4, 5 and 6. Results: The integrative review revealed the following themes: (1) interventions related to child mortality reduction, (2) implementation of maternal mortality reduction strategies, and (3) identified barriers to zero HIV and TB infections and management. Conclusion: It is recommended that poverty relief mechanisms be intensified to improve the socio-economic status of women. There is a need for sectoral planning towards maternal health, and training of healthcare workers should emphasise the reduction of maternal deaths. Programmes addressing the reduction of maternal and child mortality rates, HIV, STIs and TB need to be put in place. Keywords: Millennium Development Goals; maternal and child morbidity and mortality; HIV and AIDS; STI and TB